2018
DOI: 10.1093/jnci/djy155
|View full text |Cite
|
Sign up to set email alerts
|

Agnostic Pathway/Gene Set Analysis of Genome-Wide Association Data Identifies Associations for Pancreatic Cancer

Abstract: Background: Genome-wide association studies (GWAS) identify associations of individual single-nucleotide polymorphisms (SNPs) with cancer risk but usually only explain a fraction of the inherited variability. Pathway analysis of genetic variants is a powerful tool to identify networks of susceptibility genes. Methods: We conducted a large agnostic pathway-based meta-analysis of GWAS data using the summary-based adaptive rank truncated product method to identify gene sets and pathways associated with pancreatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…In addition, PDAC development requires the involvement of various signal transduction pathways including the Hippo, Hedgehog, Wnt/Notch, JNK, PI3K, K-ras, and transforming growth factor (TGF) -β signaling pathways. Moreover, genome-wide association studies (GWAS) have identified a large number of pathways and gene sets involved in the development of PDAC (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, PDAC development requires the involvement of various signal transduction pathways including the Hippo, Hedgehog, Wnt/Notch, JNK, PI3K, K-ras, and transforming growth factor (TGF) -β signaling pathways. Moreover, genome-wide association studies (GWAS) have identified a large number of pathways and gene sets involved in the development of PDAC (8,9).…”
Section: Introductionmentioning
confidence: 99%
“…However, pinpointing the causative variation is more di cult. To reveal the mechanism through which a mutation site affects a phenotype and to perform subsequent functional research, GWAS joint analysis on multiple genomic levels can be used and biological pathway analysis can be applied to detect the superposition of multiple minor genes by examining genes involved in the same biological pathway, thus enabling deeper mining of GWAS data [10][11][12][13]. With the development of genome sequencing technology and the continuous improvement of statistical methods, GWAS is expected to be more e ciently applied to gene identi cation for important traits in livestock and poultry and to play an increasingly important role in animal breeding.…”
Section: Introductionmentioning
confidence: 99%
“…Pancreatic ductal adenocarcinoma (PDAC) is one of the most fatal cancers in the world with the worst prognosis, and its incidence has increased in recent years 1 . To date, the rate of pancreatic cancer incidence nearly equals its mortality due to diagnosis at later stage and the lack of early detection markers 2 .…”
Section: Introductionmentioning
confidence: 99%